Ecotoxicological impact of graphene oxide: toxic effects on the model organism Artemia franciscana. Issue 11 (21st October 2020) - Cavion, Federica; Fusco, Laura; Sosa, Silvio; Manfrin, Chiara; Alonso, Beatriz; Zurutuza, Amaia; Della Loggia, Roberto; Tubaro, Aurelia; Prato, Maurizio; Pelin, Marco
Abstract : The environmental impact of graphene oxide was evaluated on the model organism Artemia franciscana for ecotoxicological studies considering different biological parameters. Abstract : Given the numerous potential applications of graphene oxide (GO) and its consequent release into the environment, this study was carried out to assess the toxic effects of GO on Artemia franciscana, a well-established model organism for marine ecotoxicological studies. A. franciscana stage I nauplii or adults were exposed to GO (1–100 μg mL −1 ) up to 72 h, which induced a significant mortality only in adults exposed to the highest concentration for 72 h. The susceptibility of adults to GO was further investigated evaluating other biomarkers of toxicity: already 24 h exposure to 100 μg mL −1 GO induced significant activation of the xenobiotic detoxifying and antioxidant enzyme glutathione S -transferase, whereas other toxicological parameters, such as reactive oxygen species (ROS) production, cholinesterase activity and growth rate, were not affected even after 72 h exposure. Furthermore, the uptake of GO was studied in relation to food supplement: GO accumulation in the digestive tract was lower in the presence of food, with respect to non-fed organisms. In conclusion, this study highlights the weak toxic effects of GO on A. franciscana adults, lower than those induced by other carbon-based materials. However, this suggests a possible ecotoxicological impact of GO that needs to be further studied.